Preparation method and application of high-entropy garnet type oxide solid electrolyte film
By doping elements such as gallium, titanium, tantalum and niobium into the garnet oxide solid electrolyte and using spin coating and sintering technology, a high-entropy garnet oxide solid electrolyte film was prepared, which solved the ions of traditional electrolytes at room temperature. The problems of low conductivity and poor air stability have achieved a high-performance solid electrolyte film.
Patent Information
- Application Number
- CN202411616168.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional garnet oxide solid electrolytes have problems such as low ionic conductivity, poor air stability, high sintering temperature and energy consumption at room temperature, and it is difficult to prepare thinner electrolyte sheets.
By doping elements such as gallium, titanium, tantalum and niobium to the lithium and zirconium sites of LLZO, and combining with spin coating and sintering technology, a high-entropy garnet oxide solid electrolyte film was prepared, with the chemical formula Li5 .25Ga0.25La3(ZrTiTaNb)0.5O12.
The high entropy garnet oxide solid electrolyte film has achieved room temperature high ion conductivity, good air stability, low sintering temperature and energy consumption, excellent interfacial wetting and lithium dendrites suppression ability, and the comprehensive performance is significantly better than that of Traditional electrolytes.
Smart Images

Figure CN119447437A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of garnet solid-state lithium battery design, and in particular to a preparation method and application of a high-entropy garnet-type oxide solid electrolyte film. Background Art
[0002] All-solid-state lithium batteries use solid electrolytes instead of traditional flammable and leaky liquid electrolytes, which have higher safety and energy density and show broad development prospects. Solid electrolytes have been widely studied as key components of all-solid-state lithium batteries. Garnet-type oxide solid electrolytes (Li7La3Zr2O 12 LLZO) has attracted the attention of researchers due to its good stability and wide electrochemical window with metallic lithium (Li) anode, but its cubic phase structure with high ionic conductivity at room temperature is unstable and easily reacts with water and CO2 in the air, and has problems such as low ionic conductivity at room temperature, poor air stability, high sintering temperature and energy consumption.
[0003] Doping LLZO with elements can increase the lithium vacancies and Li + The disorder of the skeleton improves its performance. However, the final effect of doping modification often depends on the type of doping elements and their doping level. The improvement effect of a single element on the performance of LLZO electrolyte is usually limited and single. For example, Ti doping can only inhibit lithium dendrites by promoting the sintering of electrolyte particles to increase density, and Ta / Nb doping can only improve ionic conductivity. In addition, although the traditional pressing and sintering method can improve the density of the electrolyte sheet to a certain extent, it is difficult to press out a thinner electrolyte sheet during the sheeting process because a sheet that is too thin is easily damaged during the demolding process. Therefore, the electrolyte sheet obtained by this method is usually thicker, and the surface of the electrolyte sheet needs to be polished after high-temperature sintering to improve its interface contact with the lithium negative electrode.
[0004] "High entropy" materials are a class of single-phase materials proposed in recent years, which are obtained by solid solution of five or more elements in an equimolar ratio or a near molar ratio. At present, the design strategy of high entropy materials has been extended to various functional ceramic materials, such as oxides, sulfides, carbides, nitrides, borides and silicates. Among them, high entropy oxide materials show unique advantages in the field of energy storage and conversion. Specifically, the difference in the atomic size of different elements and their bonding energy with oxygen ions in high entropy oxide materials will lead to local distortion of the lattice structure, thereby improving the migration of ions in the material. In addition, the high entropy effect brought by multiple elements and the synergistic effect between elements can also effectively improve the performance of the material. Therefore, the simultaneous introduction of multiple suitable elements into the structure of LLZO to construct a high entropy garnet solid electrolyte may produce unexpected modification effects.
[0005] In addition, spin coating, as a wet chemical film-making process, has the advantages of mild and flexible synthesis conditions, uniform film formation with controllable thickness and composition, simple process, low cost, and high yield. Therefore, using spin coating to prepare solid electrolytes into thin-film materials will be more conducive to ion migration in the electrolyte, make up for the shortcomings of LLZO in ionic conductivity, and reduce the overall impedance of the battery. Summary of the invention
[0006] The present invention provides a preparation method and application of a high entropy garnet oxide solid electrolyte film. In order to make up for the shortcomings of traditional garnet electrolytes, four elements, gallium (Ga), titanium (Ti), tantalum (Ta), and niobium (Nb), are innovatively selected to simultaneously dope and replace the lithium site and zirconium site of LLZO, and combined with a spin coating sintering process, a Li / Zr dual-site substituted high entropy garnet oxide solid electrolyte film (chemical formula Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 ).
[0007] To achieve the above object, the present invention provides a method for preparing a high entropy garnet oxide solid electrolyte film, wherein the high entropy garnet oxide solid electrolyte is Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 , the preparation method comprises the following steps:
[0008] S1, according to the general formula Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 The stoichiometric ratio of the elements in the quartz crystal was adjusted, and the lithium Li site and zirconium Zr site of LLZO were simultaneously doped and replaced by gallium Ga, titanium Ti, tantalum Ta, and niobium Nb to prepare a high entropy garnet-type oxide solid electrolyte powder.
[0009] S2. Spin-coating the high entropy garnet-type oxide solid electrolyte powder prepared in step S1 onto a silicon substrate and sintering the powder to form a film, thereby preparing a high entropy garnet-type oxide solid electrolyte thin film.
[0010] Preferably, the specific method of doping substitution in step S1 is:
[0011] S1-1, dispersing stoichiometric amounts of lithium carbonate, gallium trioxide, lanthanum trioxide, zirconium dioxide, titanium dioxide, tantalum pentoxide and niobium pentoxide precursors in an anhydrous ethanol solution, and mixing them uniformly by ball milling to obtain a mixture;
[0012] S1-2, drying the mixture obtained in step S1-1 in a 120° C. forced air oven for 12 h, and then pre-sintering at 950° C. for 6 h, and re-dispersing the pre-sintered powder in an anhydrous ethanol solution and mixing by ball milling;
[0013] S1-3. Place the sample after the secondary ball milling in step S1-2 in a 120° C. forced air oven and dry for 12 hours to obtain a high entropy garnet oxide solid electrolyte powder after grinding.
[0014] Preferably, Li2CO3 needs to be in excess of 10 wt% to compensate for the volatilization of lithium during the subsequent high-temperature heating process, and La2O3 must be dried at 900°C for 10 h before use.
[0015] Preferably, in step S2, the spin coating is: dispersing the high entropy garnet oxide solid electrolyte powder in anhydrous ethanol solution to prepare a 1 g / 100 mL dispersion; dropping the dispersion onto the silicon substrate, and coating the film using a spin coating mill.
[0016] Preferably, the spin coating process parameters are: spin coating times 10 times, spin coating speed 3000 rpm, and spin coating time 30 s / time.
[0017] Preferably, in step S2, sintering is as follows: placing the spin-coated silicon substrate into a muffle furnace at 3°C·min -1 The temperature is raised to 1060°C at a heating rate of 1000°C and sintered for 1 hour. After the sintering, it is naturally cooled to room temperature. The obtained high-entropy garnet-type oxide solid electrolyte film is cut and set aside according to the needs.
[0018] Preferably, the thickness of the high entropy garnet oxide solid electrolyte film is 0.19 to 0.22 mm.
[0019] The preparation method and application of a high entropy garnet oxide solid electrolyte film of the present invention have the following beneficial effects:
[0020] (1) Compared with traditional garnet oxide solid electrolyte sheets, the high entropy effect and cocktail effect generated by multiple elements in the high entropy garnet oxide solid electrolyte film give it excellent comprehensive properties such as high room temperature ionic conductivity, good air stability, low sintering temperature and energy consumption, good interface wettability and lithium dendrite suppression ability;
[0021] (2) The spin coating film forming process adopted has the advantages of mild and flexible synthesis conditions, uniform film formation with controllable thickness and composition, simple process, low cost and high yield;
[0022] (3) The thickness of the electrolyte film is significantly lower than that of the traditional electrolyte sheet and the film has a certain mechanical flexibility, which will be beneficial to its application in micro wearable devices;
[0023] (4) The high-entropy garnet oxide solid electrolyte film constructed by the present invention can solve the problems existing in traditional garnet oxide solid electrolyte sheets at low cost and high efficiency, and will further promote the application and development of high-performance garnet all-solid-state lithium batteries in micro wearable devices.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD spectrum of LGLZTTNO high entropy garnet oxide solid electrolyte film;
[0026] Figure 2 The Raman spectra of LGLZTTNO high entropy garnet oxide solid electrolyte film and LLZO garnet oxide solid electrolyte sheet after being placed in air for 15 days;
[0027] Figure 3 This is the EIS graph of LGLZTTNO high entropy garnet oxide solid electrolyte film at room temperature;
[0028] Figure 4 The EIS graph of the Li / LGLZTTNO / Li lithium symmetric battery assembled with LGLZTTNO high entropy garnet oxide solid electrolyte film at room temperature;
[0029] Figure 5 The critical current density (CCD) diagram of Li / LGLZTTNO / Li lithium symmetric battery assembled by LGLZTTNO high entropy garnet oxide solid electrolyte film at 60°C;
[0030] Figure 6 This is the cycling stability diagram of the Li / LGLZTTNO / Li lithium symmetric battery assembled with LGLZTTNO high entropy garnet-type oxide solid electrolyte film at 60°C. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0032] Embodiment 1
[0033] (I) Li 5.25 Ga0.25 La3(ZrTiTaNb) 0.5 O 12 Synthesis of high entropy garnet oxide solid electrolyte powder
[0034] S1. According to the stoichiometric ratio, 12.277 g of lithium carbonate (Li2CO3), 1.351 g of gallium trioxide (Ga2O3), 28.124 g of lanthanum trioxide (La2O3), 3.584 g of zirconium dioxide (ZrO2), 2.302 g of titanium dioxide (TiO2), 6.357 g of tantalum pentoxide (Ta2O5) and 3.827 g of niobium pentoxide (Nb2O5) were dispersed in 120 g of anhydrous ethanol solution and heated at 200 r·min. -1 The mixture was mechanically ball milled at a speed of 1000 nm for 17.5 h to achieve uniform mixing.
[0035] Among them, Li2CO3 needs to be in excess of 10wt% to compensate for the volatilization of lithium during the subsequent high-temperature heating process, and La2O3 must be dried at 900℃ for 10h before use.
[0036] S2. The obtained mixture was dried in a forced air oven at 120° C. for 12 h and then pre-sintered at 950° C. for 6 h.
[0037] S3: The pre-sintered powder was dispersed again in an appropriate amount of anhydrous ethanol solution and heated at 200 r / min. -1 Mechanical ball milling was carried out at a speed of 17.5 h.
[0038] S4. The sample after the second ball milling was placed in a 120°C blast oven and dried for 12 h. Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 The precursor powder is bagged for later use.
[0039] (II) Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 Synthesis of high entropy garnet oxide solid electrolyte films
[0040] S1, first take 1g of Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 The precursor powder was placed in 50 mL of anhydrous ethanol solution for ultrasonic dispersion, and anhydrous ethanol was continued to be added to the dispersed solution and ultrasonic treatment was performed to adjust the volume to 100 mL to obtain a uniform dispersion with a concentration of 1 g / 100 mL.
[0041] S2. Add the prepared dispersion liquid to the silicon substrate and use the optional coating mill to coat the film. The spin coating process parameters are: 10 times of spin coating, 3000 rpm of spin coating speed, and 30 s / time of spin coating.
[0042] S3. Use flat tweezers to take out the sprayed silicon substrate and put it into a muffle furnace. Heat it to 1060°C at a heating rate of 3°C / min and sinter it for 1 hour, then cool it naturally to room temperature.
[0043] S4. After the high temperature heat treatment, the obtained sample was cut to obtain a Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 The high entropy garnet-type oxide solid electrolyte film was stored in an Ar2-filled glove box until use.
[0044] Embodiment 2
[0045] Using Li in Example 1 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 The high entropy garnet oxide solid electrolyte film (LGLZTTNO) is used to prepare Li / LGLZTTNO / Li symmetric batteries. The specific preparation process is as follows:
[0046] (1) In a glove box filled with Ar2 atmosphere, a sandwich-shaped stack of lithium (Li) sheets, LGLZTTNO, and lithium (Li) sheets were heated at 300°C for 30 minutes to make the lithium sheets adhere to the surface of the electrolyte film. The diameter and thickness of the lithium sheets were 8 mm and 0.5 mm, respectively.
[0047] (2) The spring, stainless steel disk, and electrolyte with lithium sheet attached were assembled into a CR2025 button cell and sealed using a hydraulic press with a sealing pressure of 50 kg cm -3 .
[0048] Experimental testing
[0049] (1) X-ray diffraction (XRD) test.
[0050] The crystal structure, lattice parameters, crystal defects, etc. of the LGLZTTNO high entropy garnet oxide solid electrolyte film were characterized by X-ray diffractometer (XRD, Rigaku Smart Lab, Cu Kαradiations). The corresponding characteristic peaks collected by the XRD test were compared with the annotated cards in the database to determine whether the desired product phase was generated.
[0051] like Figure 1 As shown, it is illustrated that Example 1 combines high entropy doping with a spin coating process to successfully prepare a Li / Zr dual-site substituted high entropy garnet-type oxide solid electrolyte film LGLZTTNO with a thickness of about 0.2 mm and a pure cubic phase structure at room temperature.
[0052] (2) Raman spectroscopy test.
[0053] The crystal structure and air stability of LGLZTTNO high entropy garnet oxide solid electrolyte film were characterized by Raman spectroscopy (Thermo Fisher Scientific DXRxi). Raman shift depends only on the structure of the scattering molecules. According to the peaks formed on the Raman shift, the different chemical bonds in the phase can be qualitatively characterized, thereby proving the existence of certain impurity phases with a small content.
[0054] The results are as follows Figure 2 As shown in the figure, it can be seen that the Raman spectrum curve of the LGLZTTNO high entropy garnet oxide solid electrolyte film synthesized in Example 1 is about 720cm compared with the LLZO garnet solid electrolyte sheet obtained by traditional tablet pressing and sintering. -1 The peak intensity at the wave number is significantly enhanced, which is mainly due to the fact that a large number of Ti / Ta / Nb atoms replace the Zr atoms in the LLZO crystal structure and form Ti / Ta / Nb-O bonds.
[0055] At the same time, compared with the LLZO garnet solid electrolyte sheet obtained by traditional pressing and sintering, the Raman spectrum curve of the LGLZTTNO high entropy garnet oxide solid electrolyte film measured after being placed in the air for 15 days did not show an obvious Li2CO3 peak, indicating that it has relatively excellent air stability.
[0056] (3) Electrochemical impedance spectroscopy (EIS) test.
[0057] The electrochemical impedance spectroscopy (EIS) tests of the LGLZTTNO high-entropy garnet oxide solid electrolyte film and the lithium symmetric battery assembled therein were carried out by a battery testing system (Solaltron 1260 and 1470E) with an AC amplitude of 10mV in the frequency range of 1MHz to 0.1Hz.
[0058] The EIS test of the electrolyte film is performed by clamping it between two steel sheets. The assembled battery needs to be taken out after standing in the glove box for 12 hours, and the battery is clamped in the order of positive and negative poles for testing. The obtained EIS spectrum can be used to analyze the lithium ion transmission and impedance of the electrolyte film and battery during the charging and discharging process. The calculation formula of the electrolyte film ion conductivity is as follows:
[0059] σ=L / (πr 2 )R
[0060] Wherein: σ represents ionic conductivity; r represents the radius of the electrolyte film; R represents the measured total resistance; and L represents the thickness of the electrolyte film.
[0061] The EIS graph of LGLZTTNO high entropy garnet oxide solid electrolyte film at room temperature is shown in Figure 3 As shown in the figure, it can be seen that the LGLZTTNO high entropy garnet oxide solid electrolyte film synthesized by the present invention has a 1.26×10 - 4 S cm -1 High ionic conductivity.
[0062] The EIS graph of Li / LGLZTTNO / Li lithium symmetric battery at room temperature is shown in Figure 4 As shown in FIG. 1 , it can be seen that the interface area specific impedance of the lithium symmetric battery (Li / LGLZTTNO / Li) assembled by using the LGLZTTNO high entropy garnet oxide solid electrolyte film synthesized by the present invention is as low as 85.45 Ωcm 2 .
[0063] (4) Critical current density (CCD) test.
[0064] The assembled battery was taken out after standing in the glove box for 12 hours, and the battery was clamped in the order of positive and negative poles. The solid-state battery was subjected to an electrochemical stripping / plating test for 0.5 hours at a constant temperature of 60°C using a Neware electrochemical testing system (NEWARE CT-4000) with gradually increasing current to evaluate the critical current density (CCD) of the battery.
[0065] like Figure 5 As shown in Figure 2, the lithium symmetric battery (Li / LGLZTTNO / Li) assembled with LGLZTTNO high entropy garnet oxide solid electrolyte film has a current density of 0.96 mA cm -2 The high critical current density indicates that the electrolyte film has excellent lithium dendrite inhibition ability.
[0066] (5) Cyclic stability test.
[0067] The assembled battery was placed in the glove box for 12 h and then taken out. The battery was clamped in the order of positive and negative electrodes. The Neware electrochemical test system (NEWARE CT-4000) was used to test 0.1 mA cm at a constant temperature of 60 °C with a fixed plating / stripping interval of 1 h. -2 Long cycle performance of the battery at high current density.
[0068] like Figure 6 As shown in the figure, the lithium symmetric battery (Li / LGLZTTNO / Li) assembled with LGLZTTNO high entropy garnet oxide solid electrolyte film has a high conductivity at 0.1 mA·cm -2 It can stably cycle for more than 4500 hours at a current density of , showing excellent cycle stability.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high entropy garnet oxide solid electrolyte film, characterized in that: High entropy garnet oxide solid electrolyte for Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 , the preparation method comprises the following steps: S1, according to the general formula Li 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 The stoichiometric ratio of the elements in the quartz crystal was adjusted, and the lithium Li site and zirconium Zr site of LLZO were simultaneously doped and replaced by gallium Ga, titanium Ti, tantalum Ta, and niobium Nb to prepare a high entropy garnet-type oxide solid electrolyte powder. S2. Spin-coating the high entropy garnet-type oxide solid electrolyte powder prepared in step S1 onto a silicon substrate and sintering the powder to form a film, thereby preparing a high entropy garnet-type oxide solid electrolyte thin film.
2. The method for preparing a high entropy garnet oxide solid electrolyte film according to claim 1, characterized in that: The specific method of doping substitution in step S1 is: S1-1, dispersing stoichiometric amounts of lithium carbonate, gallium trioxide, lanthanum trioxide, zirconium dioxide, titanium dioxide, tantalum pentoxide and niobium pentoxide precursors in an anhydrous ethanol solution, and mixing them uniformly by ball milling to obtain a mixture; S1-2, drying the mixture obtained in step S1-1 in a 120° C. forced air oven for 12 h, and then pre-sintering at 950° C. for 6 h, and re-dispersing the pre-sintered powder in an anhydrous ethanol solution and mixing by ball milling; S1-3. Place the sample after the secondary ball milling in step S1-2 in a 120° C. forced air oven and dry for 12 hours to obtain a high entropy garnet oxide solid electrolyte powder after grinding.
3. The method for preparing a high entropy garnet oxide solid electrolyte film according to claim 2, characterized in that: Li2CO3 needs to be in excess of 10wt% to compensate for the volatilization of lithium during the later high-temperature heating process, and La2O3 must be dried at 900℃ for 10h before use.
4. The method for preparing a high entropy garnet oxide solid electrolyte film according to claim 1, characterized in that: In step S2, spin coating is as follows: high entropy garnet-type oxide solid electrolyte powder is dispersed in anhydrous ethanol solution to prepare a 1 g / 100 mL dispersion; the dispersion is dropped onto a silicon substrate, and an optional coating mill is used for coating.
5. The method for preparing a high entropy garnet oxide solid electrolyte film according to claim 4, characterized in that: The spin coating process parameters are: spin coating times 10 times, spin coating speed 3000 rpm, spin coating time 30 s / time.
6. The method for preparing a high entropy garnet oxide solid electrolyte film according to claim 1, characterized in that: In step S2, sintering is as follows: placing the spin-coated silicon substrate into a muffle furnace and sintering at 3°C / min -1 The temperature is raised to 1060°C at a heating rate of 1000°C and sintered for 1 hour. After the sintering, it is naturally cooled to room temperature. The obtained high-entropy garnet-type oxide solid electrolyte film is cut and set aside according to the needs.
7. The method for preparing a high entropy garnet oxide solid electrolyte film according to claim 1, characterized in that: The thickness of the high entropy garnet oxide solid electrolyte film is 0.19 to 0.22 mm.
8. A high entropy garnet-type oxide solid electrolyte film Li prepared by the method for preparing a high entropy garnet-type oxide solid electrolyte film according to any one of claims 1 to 7 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 .
9. A high entropy garnet oxide solid electrolyte film Li as claimed in claim 7 5.25 Ga 0.25 La3(ZrTiTaNb) 0.5 O 12 Application in the preparation of all-solid-state lithium batteries.